2006
DOI: 10.1007/s00425-006-0408-8
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate starvation responses are mediated by sugar signaling in Arabidopsis

Abstract: Phosphate (Pi) is one of the least available plant nutrients in soils. It is associated with dynamic changes in carbon fluxes and several crucial processes that regulate plant growth and development. Pi levels regulate the expression of large number of genes including those involved in photosynthesis and carbon metabolism. Herein we show that sugar is required for Pi starvation responses including changes in root architecture and expression of phosphate starvation induced (PSI) genes in Arabidopsis. Active pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
175
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(192 citation statements)
references
References 51 publications
16
175
0
1
Order By: Relevance
“…1B). A light dependency of the low-phosphate response has been previously observed for lupine (Lupinus albus; Liu et al, 2005) and Arabidopsis (Karthikeyan et al, 2007). Interestingly, in these and other studies (Müller et al, 2005), the effect of light was related to the carbohydrates provided via photosynthesis, because sugar addition mimicked or partially restored the low-phosphate response, even in darkness.…”
Section: Hypoxic Induction Of Galactolipid-related Genes Provides Inssupporting
confidence: 57%
“…1B). A light dependency of the low-phosphate response has been previously observed for lupine (Lupinus albus; Liu et al, 2005) and Arabidopsis (Karthikeyan et al, 2007). Interestingly, in these and other studies (Müller et al, 2005), the effect of light was related to the carbohydrates provided via photosynthesis, because sugar addition mimicked or partially restored the low-phosphate response, even in darkness.…”
Section: Hypoxic Induction Of Galactolipid-related Genes Provides Inssupporting
confidence: 57%
“…There is growing evidence that long-distance Suc transport plays an important role in phosphorous responses (Liu et al, 2005;Karthikeyan et al, 2007;White, 2008, 2011). The pho3 mutation, which was identified in a screen for reduced acid phosphatase activity during P limitations, turned out to be a mutant allele of AtSUC2 (Lloyd and Zakhleniuk, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The pho3 mutation, which was identified in a screen for reduced acid phosphatase activity during P limitations, turned out to be a mutant allele of AtSUC2 (Lloyd and Zakhleniuk, 2004). Both a reduction in photosynthesis and stem girdling, which blocks phloem transport, attenuate P deficiency responses in roots, including a decrease in the expression of many PSI genes (Liu et al, 2005;Karthikeyan et al, 2007). In addition, it was recently shown that ubiquitous SUT OE can induce a P deficiency response (Lei et al, 2011), potentially by disrupting normal Suc distribution patterns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PSI gene expression is influenced by sugar levels (Karthikeyan et al, 2006), while exogenous Suc may exacerbate Pi starvation through increased cell proliferation signaling (Lai et al, 2007). As plant cultivation under sterile conditions in the presence of exogenous Suc may generate phenotypes not seen under more physiologically relevant conditions we examined whether soil-grown atpap26 plants displayed any phenotype.…”
Section: Atpap26 Is Essential For Efficient Acclimation Of Arabidopsimentioning
confidence: 99%